Corrosion Potential of Activated Fly Ash Concrete - George, Sunilaa; Thenmozhi, R.; Magudeswaran, P.N. (Asian Journal of Chemistry, 2011)
Cement concrete is the most widely used construction material in many infrastructure projects due to its versatility. The Ministry of Power, Government of India estimates generation of 600 million tons fly ash from thermal power plants by 2031-2032 which is a major concern to environment. The utilization of fly ash as construction material largely depends on its mineral structure and pozzalonic property. These two properties of fly ash can be enhanced by different methods of activation. This paper highlights chemical activation of fly ash by using CaO and Na2SiO3 and the corrosion potential of chemically activated fly ash concrete against corrosive environment.